2021
DOI: 10.1080/14658011.2021.1890514
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically toughened EMI shielding natural rubber composite in microwave frequency bands

Abstract: Mechanically toughened high electromagnetic interference (EMI) shielding natural rubber composite material was prepared and characterised. The aim of this investigation was to reveal the role of adding cobalt nanowire and conductive graphene nanoplatelet in toughening and EMI shielding effectiveness of rubber composite in microwave bands (E, F, I and J). The composites were prepared using two roll-mill and cured at 150 ο C. The mechanical and EMI shielding behaviour was measured following ASTM standards. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It is observed that when frequency of microwave increases, wave attenuation percentage also increases for all composite designation. [ 19 ] The improvement in absorption shielding mechanism is the cause of improved conductivity of PVA composite due to the presence of Ni‐biocarbon particles. Since the biocarbon contains carbon atoms as continuous structure the eddy current development is high when the incoming microwaves hit the composite material.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that when frequency of microwave increases, wave attenuation percentage also increases for all composite designation. [ 19 ] The improvement in absorption shielding mechanism is the cause of improved conductivity of PVA composite due to the presence of Ni‐biocarbon particles. Since the biocarbon contains carbon atoms as continuous structure the eddy current development is high when the incoming microwaves hit the composite material.…”
Section: Resultsmentioning
confidence: 99%
“…8f), which represents an outstanding alternative for polymer-based composites (Fig. 8e) [2,6,[52][53][54][55][56][57][58][59].…”
Section: Electromagnetic Shielding Of the Biocompositesmentioning
confidence: 99%
“…At cryogenic conditions, the polymer matrix shrinkage was responsible to enhance the interfacial strength. The main failure mode in unidirectional [90] s samples was the interfacial debonding of fiber/matrix. Matrix shrinkage at cryogenic conditions provides a denser and brittle structure and improves tensile properties.…”
Section: Mechanical Aspects Of Thermal Shocks and Thermal Cyclesmentioning
confidence: 99%